Simulink Implementation of Digital Cascade Control DC Motor Model - A didactic approach - Kamarudin, Muhammad Nizam; Md Rozali, Sahazati (IEEE, 2008)
This paper depicts the interactive and easiest method of developing a digital cascade control model for Direct Current (DC) motor in SIMULINK environment. The development method is described step-by-step to give better understanding to electrical engineering students. The development phase focuses on the ‘hands on’ approach so that students and engineers able to follow the steps. SIMULINK/MATLAB© is used based on its reputation as a powerful tool for engineers and scientists when developing and modeling systems. Modeling phase begin with the model of a simple DC motor, a DC/DC H-bridge converter and controller design. Various control method shown in this paper provides interactive learning on how to perform conventional proportional – integral (PI) controller and intelligent self tuning PI controller using fuzzy algorithm. In the DC/DC H-bridge converter design, the significant used of a particular power electronic devices is thoroughly elaborated.